ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK HOTEL TERHADAP PENDAPATAN ASLI DAERAH KOTA BATAM - Elisabeth, Gusniar; Efriyenti, Dian (LPPM Universitas Putera Batam, 2024)
Hotel Tax, classified as a regional tax, possesses the capacity to generate revenue for PAD, thereby potentially stimulating economic growth in Batam City. Determining the efficacy and contribution of hotel tax to original regional income is the objective of this study. The research employed a quantitative descriptive methodology. The present study utilizes secondary data obtained from the Batam city Regional Revenue Agency's (Bapenda) website. The results of the research show that the growth in hotel tax revenue in the city of Batam from 2018 to 2022 has experienced fluctuations and overall the level of effectiveness of hotel taxes can be categorized as very effective, so that the effectiveness of hotel taxes is very effective on Batam City's Regional Original Income. Furthermore, the highest hotel tax contribution in the city of Batam from 2018 to 2022 experienced fluctuations. Overall, the level of hotel tax contribution can be categorized as very contributing, so that the hotel tax contribution greatly contributes to Batam City's Regional Original Income. overall hotel tax efficacy can be classified as very effective, having a positive impact on Batam City's regional original income.Additionally, there were variations in the city of Batam's greatest hotel tax contribution between 2018 and 2022.